Students Understanding of Network Virtualization in Computer Network Courses at Universitas Negeri Makassar - Arifin, Afrisal; Rezky Anisar, Muh. Alief; Baso, Fadhlirrahman; Dillah, Salsa; Muliadi, Muliadi; Surianto, Dewi Fatmarani; Parenreng, Jumadi Mabe (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2025)
Students’ understanding of network virtualization concepts in Computer Network courses remains limited, particularly in institutions with restricted access to advanced practical facilities. This study aims to analyze students’ comprehension of network virtualization and its relationship with learning experiences, technical skills, and perceptions of simulation tools. A quantitative cross-sectional survey was conducted with 202 students who had completed the Computer Network course and gained experience using Cisco Packet Tracer. The questionnaire was validated through expert judgment and construct validity testing via Exploratory Factor Analysis, and its reliability was confirmed. Findings indicate that four dimensions conceptual understanding, learning experience, technical skills, and perception of simulation tools consistently form a framework explaining students’ understanding of virtualization. Correlation analysis revealed that technical skills exert the strongest influence, while learning experiences and perceptions contribute additional support to conceptual comprehension. These results highlight the importance of integrating simulation media such as Cisco Packet Tracer into Computer Network courses, not only as a means of developing practical skills but also as a strategy to enhance students’ conceptual grasp of virtualization technologies increasingly demanded in the digital industry. This study contributes to the literature by emphasizing the cognitive dimension of simulation-based learning, an aspect often overlooked in prior research that mainly focused on technical performance.